2022
DOI: 10.7150/jca.78098
|View full text |Cite
|
Sign up to set email alerts
|

LHPP suppresses gastric cancer progression via the PI3K/AKT/mTOR signaling pathway

Abstract: Emerging evidence has revealed the anti-oncogenic role of LHPP in several malignancies. The current study aims to explore the underlying mechanism of LHPP in gastric cancer (GC). We used the TCGA and GEO databases to investigate the expression profile, prognostic value, and cellular function of LHPP in GC. LHPP expression pattern were further verified using clinical samples by immunohistochemistry and western blot analysis. Moreover, stable cancer cell lines with LHPP overexpression or knockdown were establish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 31 publications
1
4
0
Order By: Relevance
“…Subsequent studies have confirmed that LHPP expression level is negatively correlated with cell cycle progression and metastasis in human HCC tissues and forced overexpression of LHPP inhibited the growth and metastasis of various human hepatoma cells [ 15 ]. A similar tumor suppressor role has been reported in other types of cancer such as cervical cancer [ 16 ], gastric cancer [ 17 , 18 ], thyroid cancer [ 19 ], bladder cancer [ 20 ], colorectal cancer [ 21 ] and glioblastoma [ 22 ]. Therefore, restoring the function of LHPP may serve as a potential therapeutic target for HCC and other types of tumors.…”
Section: Introductionsupporting
confidence: 67%
“…Subsequent studies have confirmed that LHPP expression level is negatively correlated with cell cycle progression and metastasis in human HCC tissues and forced overexpression of LHPP inhibited the growth and metastasis of various human hepatoma cells [ 15 ]. A similar tumor suppressor role has been reported in other types of cancer such as cervical cancer [ 16 ], gastric cancer [ 17 , 18 ], thyroid cancer [ 19 ], bladder cancer [ 20 ], colorectal cancer [ 21 ] and glioblastoma [ 22 ]. Therefore, restoring the function of LHPP may serve as a potential therapeutic target for HCC and other types of tumors.…”
Section: Introductionsupporting
confidence: 67%
“…LHPP is a histidine phosphatase, and recently LHPP has been identified to be a tumour suppressor in HCC and other cancers 31,32 , which can inhibit tumour cell proliferation and metastasis, and induce apoptosis in numerous tumor cells by affecting different target genes 33 . Mechanically, tumor suppression activity of LHPP may be mediated through inhibiting EGFR 34 , modulating AKT/mTOR 35,36 and TGF-β/smad signaling pathway 18 etc. Recent study also proved that loss of LHPP is associated with intestinal inflammation in colitis mice model and inflammatory bowel disease patients 21 , showing that vital roles of LHPP in maintenance of normal body functions.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, drugs targeting the PI3K/AKT/mTOR pathway in combination with chemotherapeutic drugs are considered promising treatment approaches [ 47 ]. Several genes have been reported to influence cell cycle, apoptosis, migration, and invasion via the PI3K/AKT/mTOR signaling pathway in cancer [ 48 50 ]. Moreover, Zhang et al [ 51 ] reported that proliferation of human mesangial cells and PI3K/Akt/mTOR activation were dependent on TfR, by showing that PI3K/Akt/mTOR was inhibited by the human TfR polyclonal antibody.…”
Section: Discussionmentioning
confidence: 99%